Ninjurin 2 overexpression promotes human colorectal cancer cell growth in vitro and in vivo - Li, Gang (Aging (Albany NY), 2019)
Ninjurin 2 (NINJ2) is a novel adhesion molecule. Its expression and potential function in human colorectal cancer (CRC) cells are studied. We show that NINJ2 is overexpressed in established (HT-29) and primary CRC cells and in human colon cancer tissues. Its expression level is low in colon epithelial cells and normal colon tissues. NINJ2 shRNA or knockout (by CRSIPR/Cas9) potently inhibited human CRC cell survival and proliferation, while significantly inducing cell apoptosis. Conversely, lentivirus-mediated NINJ2 overexpression promoted CRC cell proliferation. NINJ2 co-immunoprecipitated with multiple RTKs (EGFR, PDGFRα/β and FGFR) in CRC cells and human colon cancer tissues. In HT-29 cells, RTKs’ downstream signalings, Akt and Erk, were significantly inhibited by NINJ2 shRNA or knockout, but augmented following ectopic NINJ2 overexpression. In vivo, NINJ2-silenced or NINJ2-knockout CRC xenografts grew significantly slower than the control xenografts. Akt-Erk activation was largely inhibited in CRC xenografts with NINJ2 silencing or knockout. Taken together, NINJ2 overexpression promotes CRC cell growth in vitro and in vivo.